Properties of bio-composite board made from mixture of Gigantochloa Scortechinii and Themeda Arguens (L.) hack at different ratios - Amirah Mohd Fikri (2019)
The properties of Gigantochloa Scortechinii (bamboo) and Themeda Arguens (L.) Hack (Christmas Grass) composite at different ratios and different resin content were studied. The Christmas Grass and bamboo were mixed in various ratios which were 100:0, 70:30, 50:50, 30:70, 0:100 (grass:bamboo) at 12% and 14% application of Urea formaldehyde (UF) resin to manufacture 340 x 340 x 12 mm particleboard. The particles were mixed according to respective ratios with UF resin in highly-pressurized mixture for uniform blending. The mixture was manually formed using a frame onto the square-shaped wooden mold. After cold pressed, the mat was hot-pressed using hot-pressed machine at 165°C with strains of 120 MPa, 90 MPa and 70 MPa and timing of 3 minutes, 2 minutes and 1 minute respectively. All the samples were then stored in a conditioning chamber of 20±2ºC relative humidity (RH) until constant weight was reached. The physical (basic density, thickness swelling and water absorption), mechanical (MOE, MOR, internal bonding and screw withdrawal), and thermal properties as well as the micrographs structure obtained were determined. All the testing procedures were done in accordance to European Standard (EN) and compared with minimum requirement for general uses type of specification. The result indicates that ratios and resin contents influence the properties of particleboard. Basic density, MOE, MOR and internal bonding value of particleboard made from Christmas Grass and bamboo at 70:30, 50:50 and 30:70 ratios increase with the increasing of particles ratio of bamboo and resin contents. Thickness swelling and water absorption value demonstrate contrasting result. Screw withdrawal exhibits fluctuating value. The value of final degradation point at highest temperature in thermal properties for particleboard made from Christmas Grass and bamboo indicates that the presence of cellulose fibre from particleboard contributes significant effect to thermal stability of the composites. From SEM result, it can be observed that there is a good compatibility between Christmas Grass and bamboo and UF resin in the particleboard manufactured. The fibres closely touch one another and no UF resin is observed clumped. In conclusion, particleboard made from Christmas Grass and bamboo at different ratios and resin contents can be used for general uses as they meet the minimum requirement of board according to EN Standard 312-3.